2020
DOI: 10.21203/rs.3.rs-34444/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ANGPTL4 overexpression inhibits tumor cell adhesion and migration and predicts favorable prognosis of triple-negative breast cancer

Abstract: Background: Triple-negative breast cancer (TNBC) patients have relatively poor clinical outcomes. A marker predicting the prognosis of patients with TNBC could help guide treatment. Extensive evidence demonstrates that angiopoietin-like 4 (ANGPTL4) is involved in the regulation of cancer growth, metastasis and angiogenesis. Therefore, its role in TNBC is of interest. Methods: We tested the ANGPTL4 expression level in tumor tissues by immunohistochemistry (IHC) and detected its association with the clinical fea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…ANGPTL4 is highly expressed in breast cancer, colorectal cancer, prostate cancer, liver cancer, kidney cancer and other tumours and participates in the regulation of tumour growth, redox reactions, angiogenesis, metastasis and other biological functions. Although studies have shown that the high expression of ANGPTL4 in breast cancer is beneficial to inhibit the proliferation of triple‐negative breast cancer, 21 more studies have shown that ANGPTL4 has a significant effect on lung cancer cell proliferation 22 . Recent research indicated that ANGPTL4 also participates in lipid metabolism and regulates cell energy metabolism 23 .…”
Section: Discussionmentioning
confidence: 99%
“…ANGPTL4 is highly expressed in breast cancer, colorectal cancer, prostate cancer, liver cancer, kidney cancer and other tumours and participates in the regulation of tumour growth, redox reactions, angiogenesis, metastasis and other biological functions. Although studies have shown that the high expression of ANGPTL4 in breast cancer is beneficial to inhibit the proliferation of triple‐negative breast cancer, 21 more studies have shown that ANGPTL4 has a significant effect on lung cancer cell proliferation 22 . Recent research indicated that ANGPTL4 also participates in lipid metabolism and regulates cell energy metabolism 23 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, methylation and downregulation of ANGPTL4 is associated with progression and metastasis in colon cancer (16) but overexpression is associated with progression and poor prognosis in breast cancer (17) . Breast cancers of the triple negative subtype may be different since ANGPTL4 overexpression in that context has been associated with inhibition of invasion (18) . In pancreatic cancer, ANGPTL4 overexpression has been associated with tumorigenesis (19) , cellular resistance to chemotherapy (8) , hypoxia response, and poor patient outcomes (20) .…”
Section: Introductionmentioning
confidence: 99%
“…ANPTLs in addition to regulating angiogenesis are also involved in several metabolic functions such as lipid metabolism, inflammation, hematopoietic stem cell activity, and cancer cell invasion (2,3). Among the ANPTLs, ANGPTL4 also referred as fasting-induced adipose factor (Fiaf), PPAR gamma-induced angiopoietin-related protein (PPAR gamma-AR), and PPARG angiopoietin-related protein has recently emerged as a factor that significantly modulates plasma triglyceride levels (3) overexpression of which leads to enhanced lipolysis, fatty acid oxidation and reduction in adipose tissue mass (4). ANGPTL4 concentrations in blood serum have effects on glucose homeostasis, lipid metabolism, insulin levels and preventing tumor cell adhesion and migration (3).…”
Section: Introductionmentioning
confidence: 99%